LEARN 2 MOVE 2-3: a randomized controlled trial on the efficacy of child-focused intervention and context-focused intervention in preschool children with cerebral palsy - Ketelaar, Marjolijn (BioMed Central, 2010)
BACKGROUND: Little is known about the efficacy and the working mechanisms of physical and occupational therapy interventions for children with cerebral palsy (CP). In recent years a shift from a child-focused intervention approach to a more context-focused intervention approach can be recognized. Until now the evidence on the efficacy and the working mechanisms of these interventions for children with CP is inconclusive. This study aims to evaluate the efficacy and working mechanisms of two intervention approaches compared to regular care intervention in improving mobility and self-care skills of children (2-3 years) with CP and their families: a child-focused intervention approach and a context-focused intervention approach. METHODS/DESIGN: A multi-centre, randomized controlled trial research design will be used. Ninety-four children with CP (Gross Motor Function Classification System (GMFCS) level I-IV; age 2 to 3 years), their parents, and service providers (physical and occupational therapists) will be included. During a period of six months children will receive child-focused, context-focused or regular care intervention. Therapists will be randomly assigned to deliver either a child-focused intervention approach, a context-focused intervention approach or regular care intervention. Children follow their therapist into the allocated intervention arm. After the six months study-intervention period, all participants return to regular care intervention. Outcomes will be evaluated at baseline, after six months and at a three months follow-up period. Primary outcome is the capability of functional skills in self-care and mobility, using the Functional Skills Scale of the Pediatric Evaluation of Disability Inventory (PEDI). Other outcomes will be quality of life and the domains of the International Classification of Functioning, Disability and Health - for Children and Youth (ICF-CY), including body function and structure, activities (gross motor capacity and performance of daily activities), social participation, environmental variables (family functioning, parental empowerment). DISCUSSION: This paper presents the background information, design, description of interventions and protocol for this study on the efficacy and working mechanisms of child-focused intervention approach and context-focused intervention approach compared to regular care intervention in mobility and self-care skills of children (2-3 years) with CP. TRIAL REGISTRATION: This study is registered in the Dutch Trial Register as NTR1900